Explaining parents' school involvement: The role of ethnicity and gender in the Netherlands. Issue 5 (2nd September 2016) - Fleischmann, Fenella; de Haas, Annabel
ABSTRACT: Ethnic minority parents are often less involved with their children's schooling, and this may hamper their children's academic success, thus contributing to ethnic educational inequality. The authors aim to explain differences in parental involvement, using nationally representative survey data from the Netherlands of parents of primary school-aged children of Dutch, Turkish, and Moroccan origin. Descriptive findings show lower levels of parental involvement across several domains among ethnic minority compared to Dutch majority parents. Moreover, mothers are significantly more involved than fathers. To explain ethnic and gender gaps in parental engagement, the authors draw on parents' skills and household resources, parenting goals, and self-efficacy as important antecedents for their motivation to become involved. The model explains substantial portions of the variance in parental involvement and succeeds in fully explaining ethnic discrepancies by parents' levels of education and language proficiency. However, the gender gap in parental involvement remains unexplained.